2003
DOI: 10.1016/s0960-9822(03)00246-x
|View full text |Cite
|
Sign up to set email alerts
|

African Y Chromosome and mtDNA Divergence Provides Insight into the History of Click Languages

Abstract: African Y Chromosome and mtDNA Divergence Provides Insight into the History of Click Languages In the article by Knight et al. on pages 464-473 of the March 18 issue, Haplogroup E3b was omitted from the column headings in Table 1. As a result, E,D and C,F were shifted one column to the left. A corrected Table 1 is available at http://www.stanford.edu/‫ف‬aknight/ Click/. The article has also been corrected on the Current Biology web site. Additionally, the Biaka haplotype at the extreme left of the M112 median-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 0 publications
2
60
0
Order By: Relevance
“…Before this contact, separation of eastern and southern African populations is likely to have occurred at least 15 ka, and may have occurred as early as 40-50 ka, with little subsequent gene flow (10,13,14,25). The apparent molecular age and distribution of the M293 haplogroup underscores that this locus is exceptionally informative with regards to the context of this important inter- Table 1 are indicated by cross hatches.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Before this contact, separation of eastern and southern African populations is likely to have occurred at least 15 ka, and may have occurred as early as 40-50 ka, with little subsequent gene flow (10,13,14,25). The apparent molecular age and distribution of the M293 haplogroup underscores that this locus is exceptionally informative with regards to the context of this important inter- Table 1 are indicated by cross hatches.…”
Section: Resultsmentioning
confidence: 99%
“…The relatively high frequency of M35* in both eastern (e.g., Sandawe, Datog, Maasai) and southern (e.g., Kxoe) African populations is intriguing given previous studies showing substantial isolation between the two regions (10,11,13,14). Jointly, these studies suggest two temporally distinct migration events between the regions.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…12,[31][32][33] The data set includes 39 populations from the major language groups: Khoisan (!Kung1, !Kung2, Khwe, Hadza), Nilo-Saharan (Kanuri, Songhai, Turkana, Nubian, Sudanese, Mbuti, Datoga), Afroasiatic (Moroccan Berber, non-Berber Moroccan, Egyptian, Algerian Mozabite, Tuareg, Somalian, Amhara, Hausa, Podokwo, Mandara, Uldeme, Iraqw), Niger-Congo non-Bantu (Fulbe ¼ Fulfulde, Yoruba, Serer, Wolof, Mandinka, Tupuri), and Niger-Congo Bantu (Bubi, Fang, Biaka, Kikuyu, Mozambique1, Mozambique2, Bakaka, Bassa, Mbenzele, Sukuma) ( Figure 1). Some populations represented in the original data sets 12,31 -33 were omitted because they are not found on the African mainland, are Cameroonian populations not represented in the Y chromosome data set, 33 or because linguistic designations could not be inferred.…”
Section: Mtdnamentioning
confidence: 99%
“…The approximate location of 40 populations typed for Y chromosome markers in this study (K) and 39 populations surveyed for HVS1 sequence data 12,31,32,33 (J) are indicated. The distribution of the four African language families was constructed using Greenberg's 39 classifications and further refined with data from the ethnologue (http://www.ethnologue.com/).…”
Section: Mantel Testsmentioning
confidence: 99%